2015
DOI: 10.3141/2490-01
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Driver Response and Traffic Evolution under Variable Speed Limit Control

Abstract: Field test results of a variable speed limit (VSL) control algorithm, a speed-controlling algorithm using shock wave theory (SPECIALIST), were analyzed to elucidate driver response and traffic flow evolution under VSL control. Successful VSL control was characterized by nearly constant, or decreasing, demand over time. In contrast, failed VSL control was attributed to ( a) significant increase in demand (during control) and ( b) significant net inflow from ramps. The demand increase was found to be the leading… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 19 publications
0
4
0
Order By: Relevance
“…Field evaluation of VSL systems has been performed to assess the traffic flow performance [1,3,[17][18][19][20][21][22][23][24][25][26][27][28][29], driver's compliance [18,28,30,31], and safety [3,13,22,26,27,32]. Depending on the length of the motorway and available VSL system activation data, the effectiveness of the system is often analyzed in comparative terms of the changes involved in the flow-speed-density relations [1,17,24,33].…”
Section: State Of the Artmentioning
confidence: 99%
“…Field evaluation of VSL systems has been performed to assess the traffic flow performance [1,3,[17][18][19][20][21][22][23][24][25][26][27][28][29], driver's compliance [18,28,30,31], and safety [3,13,22,26,27,32]. Depending on the length of the motorway and available VSL system activation data, the effectiveness of the system is often analyzed in comparative terms of the changes involved in the flow-speed-density relations [1,17,24,33].…”
Section: State Of the Artmentioning
confidence: 99%
“…With the explosive growth of car ownership, traffic congestion, environmental pollution, and frequent accidents have become urgent problems to be solved in the current society [1,2]. In order to solve the above problems, the development of environment-friendly, safe, and intelligent vehicles has become the consensus of the automotive industry [3,4].…”
Section: Introductionmentioning
confidence: 99%
“…Because they are placed at discrete locations, it is difficult to detect dynamic traffic conditions and deliver control in time. Notably, the analysis for the SPECIALIST field test revealed that control failure likely resulted from dynamic traffic conditions such as increases in demand or on-ramp inflow (Han et al, 2015). Moreover, deployment of VMSs can be very costly.…”
Section: Introductionmentioning
confidence: 99%